2010
DOI: 10.1007/s10549-010-1138-y
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and risk of postmenopausal breast cancer

Abstract: To determine if higher bone mineral density (BMD) is a risk factor for breast cancer in women age 50 years and older. 37,860 women ≥ 50-year old with no previous breast cancer diagnosis had baseline BMD assessment between January 1999 and December 2007. Cox proportional hazards models were created for time to a new breast cancer as a function of lumbar spine or femoral neck BMD quartile (1st = lowest as reference) with adjustment for relevant covariates. A secondary analysis was performed to look for an associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 28 publications
6
24
0
1
Order By: Relevance
“…The study revealed an increased breast cancer risk for the third and fourth quartiles of lumbar spine BMD and for the third quartile for femoral neck BMD after adjusting for age and HRT use [10].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The study revealed an increased breast cancer risk for the third and fourth quartiles of lumbar spine BMD and for the third quartile for femoral neck BMD after adjusting for age and HRT use [10].…”
Section: Discussionmentioning
confidence: 88%
“…The majority of the reports originate from large databases such as the Rotterdam [6], Women’s Health Initiative (WHI) [5] and Framingham [16] studies or from pivotal trials in the field of osteoporosis (SOF, FIT, DOES) [2], [7], [9], that integrated data on BMD and breast cancer incidence in the same patient (2,4–7,9). Other studies supporting the association of higher BMD with greater risk of breast cancer derived from local BMD registries that were related to breast cancer registries in the same area [8], [10]. In some of these reports BMD was shown to be associated with increased breast cancer risk after adjusting for variables representing life-time estrogen exposure (lifetime ovulation period, BMI etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Bone density may be a marker of cumulative estrogen exposure, and studies have reported positive associations between bone density and postmenopausal breast cancer risk [2, 3]. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, no correlation was demonstrated in studies that analyzed the BMD-breast cancer relationship in premenopausal women (7,18). Therefore, we did not enroll premenopausal patients in the study.…”
Section: Discussionmentioning
confidence: 98%